Development of a grapevine detached root assay for assessing pathogenicity of Cylindrocarpon spp - Pathrose, B.; Jones, E.E.; Jaspers, M.V.; Ridgway, H.J. (New Zealand Plant Protection, 2010)
An in vitro method was developed to determine the relative pathogenicity of C macrodidymum C liriodendri and C destructans isolates on grapevine roots Young feeder roots of similar age and diameter were placed individually into Petri dishes containing watersaturated silica sand with the basal cut ends of the roots inserted into tubes filled with sterile water Three isolates each of C macrodidymum and C liriodendri and two of C destructans were inoculated as mycelial plugs onto the wounded roots three replicates per isolate After 1 month all inoculated roots had dark brown lesions (range of lengths 287404 mm) that were significantly different between isolates with an isolate of C liriodendri having the longest lesions and an isolate of C destructans the shortest This assay provides a rapid in vitro method to screen large numbers of Cylindrocarpon spp isolates